The inversion effect in word recognition: The effect of language familiarity and handwriting. (August 2022) - Feizabadi, Monireh; Singh, Mehar; Albonico, Andrea; Barton, Jason J. S.
Humans have expertise with visual words and faces. One marker of this expertise is the inversion effect. This is attributed to experience with those objects being biased towards a canonical orientation, rather than some inherent property of object structure or perceptual anisotropy. To confirm the role of experience, we measured inversion effects in word matching for familiar and unfamiliar languages. Second, we examined whether there may be more demands on reading expertise with handwritten stimuli rather than computer font, given the greater variability and irregularities in the former, with the prediction of larger inversion effects for handwriting. We recruited two cohorts of subjects, one fluent in Farsi and the other in Punjabi, neither of whom were able to read the other's language. Subjects performed a match-to-sample task with words in either computer fonts or handwritings. Subjects were more accurate and faster with their familiar language, even when it was inverted. Inversion effects were present for the familiar but not the unfamiliar language. The inversion effect in accuracy for handwriting was larger than that for computer fonts in the familiar language. We conclude that the word inversion effect is generated solely by orientation-biased experience, and that demands on this expertise are greater with handwriting than computer font.